Correlation of Stature with foot Breadth at Ball and Heel from Footprint of Bangladeshi Male Medical Students - Hossain, Farhana; Ara, Shamim; Shahana, Nahid; Rahman, Sadia; Naznin, Rawshon; Morium, Umma; Maqsood, Farzana (Bangladesh Journal of Anatomy, 2016)
Context: Footprint is the impression of the sole of the foot on an even flat ground or surface which provides the dimensions of size of the plantar surface of the foot actually touching the floor or a hard surface. Assessing the height of an individual from the measurements of different dimensions of foot has always been of immense interest to anatomists, anthropologists, podiatrists and industrialists involved in designing foot wears. As ossification of the bones of the foot occurs earlier than the long bones of the lower extremity, therefore even during adolescence, stature can be predicted more accurately from foot measurements than that from the long bones of the lower limb. Therefore, it has been shown that the reliability of prediction of stature from foot dimensions is as high as that from long bones. Materials and methods: A cross sectional analytical study was carried out at the Department of Anatomy, Dhaka Medical College Dhaka, from July 2012 to June 2013. The study was conducted on 200 male medical college students of 18-25 years of age who were selected from different medical colleges of Dhaka city and their age was determined by their national ID card. Height of the students were recorded with the help of the stadiometer. To take footprint, the sole of the feet were painted with stamp pad ink. The study was planned to determine the foot breadth at ball and heel from footprint of the male Bangladeshis and to find out the correlation of stature of Bangladeshi male medical students with their foot breadth at ball and heel from footprint. Results : Significant differences were observed between breadth at ball and heel of right and left foot (P<0.001). Breadth at ball of left foot was greater than the right foot but breadth at heel was greater on the right foot than the left foot. There was highly significant correlation between stature and the breadth at ball and heel of right and left foot ( P < 0.001 ). Bangladesh Journal of Anatomy January 2016, Vol. 14, No. 1, pp. 13-17